Disentangle the effects of environment and disturbance on landscape dynamics using LANDIS forest landscape model. (November 2022) - Wu, Mia M.; He, Hong S.; Liang, Yu; Stambaugh, Michael; Fraser, Jacob S.
Abstract: Forest landscapes pattern and development are affected by environment and disturbance. Disentangling their effects is important to understanding current landscape and predicting future changes. Such studies are limited by short-term observation and sparse disturbance-history data. Spatially-explicit forest landscape modeling represents a solution to these limitations. Here, we reconstructed the 300-year-time-series (1710–2010) of post-volcanic-eruption forest landscapes experiencing periodic-typhoons in Changbai Mountain, China, using LANDIS forest landscape model. We used a factorial simulation design to quantify the main and interactive effects of environment and typhoon on forest landscape recovery. Results showed environment had dominant effects (>80%) on early recovery (1710–1760), suggesting early forest development follows deterministic community-assembly processes governed by environment. However, as forest matured, disturbance became dominant (>50%) at later-recovery stages (1860–2010). This study showed that historical landscape reconstruction reveals the full spectrum of interplays of environment, disturbance, and succession in forest ecosystems, which may not be captured by short-term studies. Highlights: We present a novel framework for reconstructing post-volcanic forest landscapes. We quantify the effects of environment and typhoon on forest landscape recovery. The environment is strong in early succession period, whereas typhoons dominate later successional stages.